MANAGEMENT OF TOMATO LEAF MINOR TUTA ABSOLUTA WITH VARIOUS TYPES OF TRAPS IN FIELD GROWN TOMATOES - Gurgaze, Abdul Rouf; Solangi, Abdul Waheed; Jam Ghulam Mustafa Sahito; Asif Ali Kaleri; Khalid Hussain Dhiloo; Jamal-U-Ddin Hajano; Mehar Ul Nissa Rais; Saima Nazish; Ali Mustafa; Muhammad Usama Mahar (Journal of Agriculture and Biology, 2025)
Tomato leaf minor (Tuta absoluta ) is a noxious insect pests of tomato crop globally, cause huge losses of tomato in every season. Therefore, the present research was conducted to evaluate effectiveness of management trapping devices for T. absoluta in tomato field. Management traps show varied significantly in their effectiveness to capture moths, maximum mean (25.25±3.52) moths were caught by delta pheromone trap followed by light traps (14.78±1.89), color sticky traps (10.23±2.67) and water pan trap (5.61±01.56), respectively. Due to maximum capture of adult in delta pheromone trap, light trap devices and cultural practices, the lowest (11.90±2.67 %) tomato leaves infestation was recorded in delta type pheromone trap followed by cultural practices (13±2.80 %), light traps (15.35±3.12 %), color sticky traps (20.00±2.80 %), water pan trap (31.13±05.56 %) and control (35.13±04.50 %). However, lowest (05.59±03.62 %) infestation tomato fruit was recorded in delta type pheromone trap followed by cultural practices (8.50±2.1 %), light traps (09.64±02.88 %), color sticky traps (13.81±03.10 %), water pan trap (19.88±03.15 %) and control (22.10±04.50 %), respectively. Results showed the highest yield (6546.60 kg/acre) was obtained in the plots where delta type pheromone traps were installed, followed by plots in which cultural practices were carried out (6476.80 kg/acre), light traps (5943.70 kg/acre), color sticky trap (5863.20 kg/acre), water pan trap (5684.30 kg/acre) and in control (5426.00 kg/acre). The maximum cost benefit ratio (4:18) from the plots where delta pheromone traps were installed followed by cultural practices (4:16), light traps (4:12), color sticky traps (4:10), water pan trap (4:07) and control (4:02), respectively. The highest adult attraction and lowest crop damage with maximum fruit production was recorded after the application delta pheromone traps with cultural practices, thus it is recommended; that the delta pheromone traps along with cultural practices are the convenient practices to monitor and control adult population of tomato leaf miner in infested tomato field.
Keywords: Tomato; Tomato leaf miner; Eco-friendly management; Cost-benefit ratio